Peningkatan kadar troponin I sebagai prognostik mortalitas pada anak dengan syok septik - Emil Salim; Munar Lubis; Yunnie Trisnawati; Gema N. Yanni; Rina A.C. Saragih; Aridamuriany D. Lubis (Majalah Kedokteran Nusantara The Journal Of Medical School, 2014)
Septic shock remains a major cause of morbidity and mortality in children admitted to pediatric intensive care unit. The incidence of septic shock increased in 30-40 years, with estimate 7% of total deaths in children due to severe sepsis and septic shock. The cardiovascular system is one of the most commonly affected organ in a state of severe sepsis and septic shock. Troponin I is a good marker for assessing the extent of heart muscle damage and elevated levels of troponin I in sepsis patients reflects the severity of the disease, myocardial dysfunction, and poor prognosis. Septic shock patients with impaired cardiac function have an increased risk of mortality 70% to 90% when compared to patients with or without cardiac dysfunction.Keywords : septic shock; troponin I; mortality